Antimicrobial activity of tocosh (Solanum tuberosum L.) flour on Campylobacter coli strains isolated from chicken meat - Cortez R., Camila (2025)
Many studies around the world demonstrate the increase in antibiotic resistance of Campylobacter spp., which is associated with gastrointestinal problems in humans. Faced with the imminent growth of antibiotic resistance, it is important to evaluate alternative products with antimicrobial properties. Tocosh is a product used by Andean populations for its antibiotic capacity, so extracts of tocosh flour were analyzed to evaluate its antimicrobial effect against strains of Campylobacter coli. Antimicrobial effect of Tocosh flour (Solanum tuberosum L.) in 56 cryopreserved strains of Campylobacter coli isolated from chicken meat sold in Metropolitan Lima was evaluated. Aqueous and ethanolic extracts of three brands of tocosh flour (T1, T2 and T3) were obtained by partial evaporation method and their antimicrobial activity against Campylobacter coli strains was evaluated using the agar diffusion method to then find the Minimum Inhibitory Concentration (MIC). The ethanolic extract of two of the three brands of tocosh flour showed reduced inhibitory activity against Campylobacter coli strains with MIC values ranging between 43.75 mg/ml and 87.5 mg/ml. We concluded that the ethanolic extract of tocosh flour has a reduced antibacterial activity against Campylobacter coli strains.